1990
DOI: 10.1080/00103629009368357
|View full text |Cite
|
Sign up to set email alerts
|

Methods to investigate fertilization as a means to improve growth and sugar yield of sugar maple

Abstract: In a randomized block experiment, NPKCa fertilizers were applied annually for 5 years to a mature sugar maple (Acer saccharum Marsh.) woodlot in southern Ontario. Trees selected from 3 crown classes were fitted with dendrometer bands, tapped for sap and analyzed for foliar starch and nutrients and sap nutrients. Crown classes responded differently to the fertilizers. Trees which responded significantly in diameter growth did not respond the most in sugar yield. Effects of the fertilizer treatments on sugar yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
1
6
1
Order By: Relevance
“…Increased diameter increment of A. saccharum in response to additions of non-nitrogenous nutrients have been documented in many areas of north-eastern USA and Canada (Stone 1977, Hendershot and Jones 1989, Leech and Kim 1990, Hendershot 1991, Ouimet and Fortin 1992, Côté et al 1993, Côté and Ouimet 1996, Wilmot et al 1996. We detected no significant treatment effects on radial growth in either mature trees or saplings within the first 2 years of liming or P + K fertilization.…”
Section: Physiological and Growth Responsescontrasting
confidence: 40%
“…Increased diameter increment of A. saccharum in response to additions of non-nitrogenous nutrients have been documented in many areas of north-eastern USA and Canada (Stone 1977, Hendershot and Jones 1989, Leech and Kim 1990, Hendershot 1991, Ouimet and Fortin 1992, Côté et al 1993, Côté and Ouimet 1996, Wilmot et al 1996. We detected no significant treatment effects on radial growth in either mature trees or saplings within the first 2 years of liming or P + K fertilization.…”
Section: Physiological and Growth Responsescontrasting
confidence: 40%
“…For equivalent rates in our study (2 and 20 t·ha -1 ), the annual BA increased by 2.3 and 4.8% over 4 years, respectively. In previous experiments involving sugar maple, applications of mineral fertilizers (Stone 1980;Leech and Kim 1990), and lime especially (Côté et al 1995), did not always have a positive effect on tree growth. Long et al (1997) mentioned that some factors can contribute to these contradictory results: (i) nutritional imbalance given the addition of a nonlimiting element, (ii) insufficient lime or fertilizer addition, and (iii) an hurried evaluation of tree reaction.…”
Section: 101mentioning
confidence: 67%
“…Some have reported increased foliar P concentrations with fertilization (Mercer 1974;Safford and Filip 1974;Ellis 1979;Safford and Czapowskyj 1986;Fahey et al 1998;Gradowski and Thomas 2008), indicating that fertilization did significantly increase P availability. However, others (Finn and White 1966;Schmitt et al 1981;Leech and Kim 1990;Ouimet and Fortin 1992) found no such increase, which is consistent either with Psufficiency in the control trees, or with insufficient P availability relative to other added nutrients.…”
Section: Production Responses To P Fertilizationmentioning
confidence: 70%